العنف المدرسي: أسبابه وأشكاله في مراحل التعليم العام من وجهة نظر الطلاب والمعلمين: دراسة ميدانية - محمود، جيهان محمد رشاد; محروس، منال عبدالحميد; أحمد، إيمان أحمد عبدالله (جامعة نايف العربية للعلوم الأمنية, 2019)
هدفت الدراسة الحالية إلى بيان أشكال العنف الموجودة بمدارس التعليم العام بالمنطقة الشرقية بالمملكة العربية السعودية ميدانيا بهدف التعرف على أكثر أنماط العنف شيوعاً، والتعرف على مصادر وأسباب العنف المدرسي، باستخدام المنهج الوصفي لفحص عينة تتكون من (200) طالب وطالبه من طلاب المدارس الابتدائية والإعدادية والثانوية في مدارس التعليم العام والمدارس الأهلية بالمنطقة الشرقية بالمملكة العربية السعودية، منهم (90) من الذكور، أعمارهم من (6 - 18 سنة) و( 110 ) من الإناث، أعمارهن من (6 - 18 سنة) تم اختيارهم بطريقة عشوائية، وعينة تكونت من (٤٥ معلماً ومعلمة) تمثل عينة عشوائية من معلمي ومعلمات مدارس التعليم العام والمدارس الأهلية. واستخدم فريق الباحثين الاستبانة في الدراسة الاستطلاعية للتعرف على أشكال العنف؛ تمهيداً لإعداد أداة الدراسة الأساسية وهي: استبانة أسباب العنف لدى طلاب المدارس من وجهة نظر الطلاب والمعلمين، وتوصلت الدراسة إلى عدد من النتائج منها: عدم وجود فروق دالة احصائياً بين متوسط درجات الطلاب وفقاً لمتغير الجنس على جميع محاور استبانة العنف نسخة الطلاب. عدم وجود فروق دالة احصائياً بين متوسط درجات الطلاب وفقا لمتغير نوع التعليم (حكومي - أهلي) على جميع محاور استبانة العنف نسخة الطلاب فيما عدا محور العوامل الأسرية؛ حيث توجد فروق دالة احصائياً بين متوسط درجات الطلاب وهي دالة عند مستوى (0.05).
This field study seeks to shed light on the types of violence that exist in public education schools in the eastern province of the Kingdom of Saudi Arabia (KSA). It attempts to identify the most common types of violence and define the sources and causes of school-related violence. The study employs the descriptive approach for examining two random samples. The first sample includes (200) male and female students from primary, preparatory, and secondary public and national schools in the eastern province of KSA. This sample is divided into (90) males and (110) females. The students sample ages are (6-18 years). The second random sample contains (45) male and female teachers working at public and national schools. The researchers use a questionnaire in the scoping study for identifying the types of violence. Consequently, they prepared the basic tool of the study which is a questionnaire on the causes of violence against school students according to the viewpoints of students and teachers. The study presents the following findings: There are no differences of statistical significance for the average of students’ scores for the variable of gender type. This applies to all aspects of the violence questionnaire presented to students. There are no differences of statistical significance for the average of students’ scores for the variable of education type (governmental - national). This applies to all aspects of the violence questionnaire presented to students; except the family factors aspect as it shows differences of a statistical significance for the average of students’ scores. This statistical significance is (0.05).
Keywords: العنف -- العنف المدرسى -- مدارس التعليم العام -- السعودية